Comparação de procedimentos para a integração de levantamentos topográficos e levantamentos com GPS - Zás, Luis Roberto Telechea (2009)
The georeferencing consists of the description of the rural property, characteristics and confrontations, of descriptive memorial containing the border coordinates, georeferenced to the Brazilian Geodetic System following the positioning precision defined by INCRA. The perimeter survey of a rural property can be done only using GPS receivers, or only with topographical conventional techniques, among which the use of total Stations or even with mixed techniques (GPS and conventional techniques). The usage of mixed techniques is done in situations where there are obstructions in part of the perimeter and it limits the use of GPS receivers, like big and dense vegetation or protected by law forest. The most used procedure for mixed surveys, is the coordinates transportation form a start base (initial) in which its coordinates are known to a final base (end) in which are known the same elements of the start base, and the distance, heading and direction between them (azimuth). For the development of this work, different methods were applied for the transformation of the local topographical coordinates of the vertex of the polygon to get the coordinates of the same vertex in the map plan, according to 10267/01 law. This work had as a target the result comparison between different procedures, from the most traditional for coordinates transportation (Puissant, Bowring, of the rope, Gauss), as well as the method of the rotation matrix (RAPP, 1989b) and an alternative method called twodimensional transformation matrix, described in WOLF and GHILANI (1997) and URIBE (2003). The found results showed that all methods present the best class of performance when the comparison was done between the values of the vertex coordinates of the polygons obtained by the different calculation procedures with the values of the coordinates of the same vertexes of the polygon obtained with the use of GPS receiver. But when analyzed with accuracy, the method which presented less average error and less standard deviation was the Bowring, and then the Puissant, and then the rotation matrix method, and then the rope method, and then the two-dimensional matrix and the last was Gauss method.